A kinematic analysis of rowing performance during a 2000m ergometer test - Simoes, M.; Veloso, A.; Armada da Silva, P. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The aim of this study was to investigate how force, velocity and power change during a maximum 2000m-rowing test, and to examine the relationship between 2-D joint kinematics and performance. Ten male rowers performed a 2000m test, which was analysed in five periods, considering also the mean final results. One-way ANOVA for repeated measures showed that force, velocity and power changed significantly along the 2000m test. Hip, and elbow joint kinematic parameters remained unchanged throughout the test but knee's angular displacement and angular position at the catch, changed significantly during the 2000m test. A stepwise multiple regression analysis evidenced that the knee angular position at the catch is in relationship with time to finish the 2000m rowing and remained the single predictor of performance.